The Effect of Different Frying Methods and the Addition of Potassium Aluminum Sulfate on Sensory Properties, Acrylamide, and Oil Content of Fried Bread (Youtiao) - Yung-Shin Shyu; Jean-Yu Hwang; Shih-Ting Shen; Wen-Chieh Sung (Applied Sciences, 2021)
This study aims to compare traditional, vacuum, and electrostatic frying methods on the mitigation of acrylamide formation, and oil content with and without potassium aluminum sulfate in youtiao. The results obtained showed that the addition of potassium aluminum sulfate decreased pH and 79.88% acrylamide content in youtiao with traditional frying. Electrostatic frying and vacuum frying methods do not reduce acrylamide content and oil content of youtiao when compared to the traditional deep-frying method in this research. The present study indicated that the pH of youtiao with vacuum frying method increased from 5.87 to 6.49 without potassium aluminum sulfate addition. Youtiao with potassium aluminum sulfate fried by traditional deep-frying had higher flavor and appearance score and lower oil content than the electrostatic frying method. The results of this research could be a consideration for alternative slow acting aluminum acidulants, reducing oil adsorbing frying methods in future work.